Factors influencing individuals' gambling behavior : a case study in Malaysia - Woon, Chan Yei (Universiti Malaysia Sarawak (UNIMAS), 2011)
Factors influencing individual gambler’s decision making may differ because of different country, races, religion and culture of residents. The main aim of this study was to investigate the factors influencing individuals’ gambling behavior. Moreover, it intends to determine whether external factors (marketing activities, sociocultural environment) or internal factors (psychological field) which consist as independent variable have positive influence on individuals’ gambling behavior (dependent variables). Theory of Buyer Behavior introduces by Howard and Sheth (1969) were used to examine consumer decision making in this study. The scope of this study was limited to casino visitors above 20 years old in Genting Highlands, Malaysia. A total of 200 filled questionnaires were analyzed. The results of Linear Regression analysis showed that Hypotheses 1 and Hypotheses 2 were accepted. Marketing activities (H1) and sociocultural environment (H2) are significant influence on individuals’ gambling behavior. Hypotheses 3 were rejected. It means Psychological Field (H3) insignificantly influences individuals’ gambling behavior. Besides, the Pearson R Correlation analysis supported the Linear Regression analysis findings that there were significant and positive relationships among independent variables and dependent variables. From the discussion, this study suggested that marketers should focus more on marketing activities and sociocultural environment since these factors provides highly influencing power in gambling behavior.